THE BEAUTY OF JINAS IN THE BOOK OF MIRQAT AL-MAHABBAH - Deuis Sugaryamah; Edi Komarudin (Al-Tsaqafa : Jurnal Ilmiah Peradaban Islam, 2019)
Mirqat al-Mahabbah is a monumental work of a great scholar, KH. Aon Abdul Majid who was well-known as Ajengan Aon from Singaparna – Tasikmalaya  and lived during the Indonesian independence struggle (1890-1934). This book is presented in Arabic language, laden with the beauty of the sentences. Using Ilmu Badi’, the beauty of a sentence can be derived either from the “words” which is called al-Muhassinat al-Lafzhiyyah, and/ or the beauty that derived from the “meaning” known as al-Muhassinat al-Maknawiyah. Among the types of beauty referencing the words are jinas, iqtibas and saja'. This study focuses on discussing the beauty of the phrases/ sentences in Mirqat al-Mahabbah only from jinas. The results indicate the varieties of jinas diverse in the book, thus symbolizing the aesthetic of such literary work.